Women in transition: The dynamic effects of inward FDI on female employment in the economy and across sectors - Pascal L. Ghazalian (Economies, 2024)
This paper examines the effects of inward Foreign Direct Investment (FDI) on the female employment rate in the economy and the share of female employment across sectors. The empirical analysis is implemented through the Generalized Method of Moments (GMM) System estimator for dynamic panel models using different empirical specifications and FDI openness indicators. The main results show that the overall effects of inward FDI on the national female employment rate are not statistically significant. However, they reveal that inward FDI has promoted the share of female employment in the service sector and has led to decreases in the share of female employment in agriculture. The FDI effects on the share of female employment in the industrial sector are found to be statistically insignificant. These results are generally supported when running the empirical analysis through alternative FDI openness indicators. Also, supplementary analysis reveals some variations in the magnitude of these effects over different national income categories. The findings in this paper emphasize FDI's gendered influences in the labour market. They are consistent with the prevalence of macroeconomic channels through which inward FDI impacts female employment across sectors, and they encompass the underlying implications of various counteracting microeconomic factors.
Keywords: 330; female employment; foreign direct investment; gender inequality; multinational enterprises; economic development; dynamic panel model